ASSESSMENT OF QUALITY OF LIFE IN CHRONIC KIDNEY DISEASE PATIENTS USING THE KIDNEY DISEASE QUALITY OF LIFE-SHORT FORMTM QUESTIONNAIRE IN INDIAN POPULATION: A COMMUNITY BASED STUDY - R, Murali; D, Sathyanarayana; Ma, Muthusethupathy (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: The objective of this study is to measure the quality of life (QOL) among the chronic kidney disease patients undergoing hemodialysis and peritoneal dialysis. Methods: The present study is observational and prospective, multicentered in an ambulatory setup located in Chennai, South India during November and December 2013. A total 50 patients were observed by using kidney disease QOL short formTM (KDQOL-SFTM) questionnaire. Results: A total of 50 end-stage renal disease (ESRD) subjects were enrolled in the present study, 56% and 44% subjects were on hemodialysis and peritoneal dialysis, respectively. In the present study, 58% were of male subjects and 76% of them were married. About 78% of subjects had diabetes mellitus as single comorbid. The present study assessed all the four domains of KDQOL in the study subjects. Physical health (PH) was significantly affected among all the four domains of the KDQOL and an average score was found to be 25.45Â±11.85 (p<0.0015). The average value of 71.93Â±12.35% (p<0.029) subjects were having satisfaction with dialysis care, which is lower than the recommended value of <65%. Conclusion: The present study revealed that ESRD patients have a poor QOL and most the affected domain is PH, hence measuring and monitoring these aspects of QOL could lead to a more patient-centered care and improve the health and well-being among patients with chronic renal failure. Keywords: Chronic kidney disease, Health related quality of life, Kidney disease quality of life-short formTM, Hemodialysis, Urea reduction ratio